The Propagation Impulse-Response Effect of Macroeconomics Variables and your Impacts in the Accounting Information - Cunha, Matheus Vieira da; Souza, Romina Batista de Lucena de; Vendruscolo, Maria Ivanice; Halmenschlager, Vinícius (Advances in Scientific and Applied Accounting, 2024)
Objective: To analyze how the impulse-response effect of macroeconomic variables impacts on solvency indicators of regulated and unregulated publicly traded companies listed on Brazil, Stock Exchange, Over the Counter (B3). Method: The Autoregressive Vectors with Error Correction (VEC) model was adopted for four lags, using the Cholesky ordering. The analysis period corresponded between the first quarter of 2005 and the third quarter of 2020. The sample data of 137 institutions were treated by 5% winsorization, aggregated based on the weighted average of the sectors. Discussion: The regulated and unregulated segments presented different behavior, being unregulated institutions more impacted by the impulse-response effect compared to the regulated ones, with a tendency of the long-term economic effect in both segments. The model showed that macroeconomic variables have impacted since the first quarter after the observance of the shock, and the effect of the variable itself on the analyzed system does not always respond significantly to explain the long-term effect observed on solvency indicators, and the exchange rate (dollar) is more economically significant for the behavior of indebtedness. Contributions: The research contributes to the definition of a model for the investigation of economic cycles at the institutional level and corroborates with the academy for understanding the macroeconomic effect on accounting information.